Isa Al-Masih dalam al-Qur’an (Studi Komparatif Interpretasi Syaikh Nawawi al-Jawi dan Karel Steenbrink) - Fiqih Kurniawan (Jurnal test, 2023)
The study of the figure of the Prophet Isa is always interesting to study. The discourse that emerged was not far from basic questions, for example: Did Jesus die on the cross or not? From that question, the author intends to explain Isa in the text of the framework of the Koran along with its interpretation from two different perspectives: insider (Muslim) and outsider (non-Muslim). In this study, the authors involved two interpreters, namely, Sheikh Nawawi and Karel Steenbrink. This paper is a literature review (library research). The research method used is descriptive-analytical and comparative. To describe this study, the author uses the maudhu'i approach, which means an effort to collect verses related to the theme of the discussion and then analyze them. As a result, Sheikh Nawawi's interpretation is more reductive and static without critically and strictly sorting the information presented in his interpretation. On the other hand, Karel Steenbrink elaborated on various relevant sources so that he could produce new meanings based on critical questions.